Evaluasi Tentang Pemungutan Pajak Bumi Dan Bangunan Sebagai Pendapatan Pajak Daerah Di Kota Jambi - Muhrizal, Muhrizal; Iqbal, Johandri; Adinda, Pramesti Nurul (LP2M Politeknik Jambi, 2024)
The influence of the evaluation of land and building tax collection carried out by the government in carrying out its rights and obligations as a fiscus, especially in the regional sector of Jambi City entitled